Peran Pemerintah Daerah Provinsi Kepulauan Riau Dalam Perlindungan Anak - Sakiman Hidayat Ansanoor (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2017)
Children play a pivotal role in a country’s development. Indonesia has given security and protection towards each child in the country, in which it is part of the government policy and it has been billed as part of the State Law. In this case Act 34 2015, discusses about the changes of Act 23, 2002 in Children’s Protection which given the order to the regional government to execute the Children’s protection in the region. Riau Archipelago Province Government has carried out its duties in providing Child Protection in the region by regulating a Region Act 7,2010 for Children’s Protection Implementation. This Region Act is still in line with Children’s Protection Act 23, 2002. However, based on the research, there are still many loopholes in this Region Act as it has not accomodateregulations about the definition of children, definition of family, definition of children’s right, repayment of expenses incurred for medical care, children with disabilities, and children from mixed marriage. Therefore, Riau Archipelago Province Government has not been able to fully perform its duties and serve its roles in providing protection to the childrenin Riau Archipelago Province. The Riau Archipelago Region Act 7, 2010 about Children’s Protection Implementation is no longer relevant to the current children’s condition in Riau Archipelago. Hence, there must be an amendment to the Region Act 7, 2010 especially in certain substances which are based on the Old Children’s Protection Act. Keywords: Children’s Protection Anak memiliki peran besar dalam pembangunan bangsa. Indonesia memberikan perlindungan kepada setiap anak, hal ini terlihat dari kebijakan pemerintah yang tertuang dalam peraturan perundang-undangan tepatnya Undang-Undang Nomor 35 Tahun 2014 tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak yang mengamatkan pemerintah daerah untuk melaksanakan perlindungan anak di daerah. Pemerintah Provinsi Kepulauan Riau telah menjalankan tugasnya memberikan perlindungan anak didaerah dengan dibentuknya Peraturan Daerah Provinsi Kepulauan Nomor 7 Tahun 2010 tentang Penyelenggaraan Perlindungan Anak. Peraturan Daerah tersebut masih merujuk pada Undang-Undnag Perlindungan Anak Nomor 23 Tahun 2002. Namun berdasarkan hasil penelitian, Perda tersebut masih memiliki terdapat banyak kekurangan karena Perda belum mengakomodir aturan tentang definisi anak, definisi keluarga, definisi hak anak, restitusi, anak penyandang disabilitas, dan anak dari perkawinan campuran. Sehingga pemerintah Provinsi Kepulauan Riau belum dapat melaksanakan tugasnya dan menjalankan perannya dalam memberikan perlindungan anak di daerah provinsi Kepulauan Riau dengan maksimal. Peraturan Daerah Provinsi Kepulauan Riau Nomor 7 Tahun 2010 tentang Penyelenggaraan Perlindungan Anak sudah tidak relevan dengan kondisi anak di Provinsi Kepulauan Riau saat ini. Oleh karena itu perlu dilakukan revisi Peraturan Daerah Nomor 7 Tahun 2010, khususnya substansi tertentu dari Perda yang dibentuk atas dasar undang-undang perlindungan anak yang lama. Kata kunci: Perlindungan Anak